REGULARITIES OF STRESS CORROSION CRACKING OF 10G2FB PIPELINE STEEL IN NEAR NEUTRAL SOIL ENVIRONMENT AT CATHODIC POLARIZATION - NYRKOVA, LYUDMILA; LISOVYI, PAVLO; GONCHARENKO, LARYSA; OSADCHUK, SVETLANA; KLYMENKO, ANATOLIY; BORYSENKO, YULIYA; BRATOCHKIN, OLEG (Technologies and Engineering, 2021)
Purpose. Investigate the regularities of corrosion cracking of 10G2FB steel under cathodic protection. Methodology. The following methods were used: slow strain rate, scanning electron microscopy, electrolytic hydrogenation, mass measurement. Results. The regularities of corrosion cracking of pipe steel 10G2FB in near neutral soil environment NS4 in the range of potentials from the corrosion potential to -1.2 V were investigated. According to the results of a complex of corrosion-mechanical, electrochemical and physical studies, it was found that with a shift in the cathodic polarization potential in the range of -0,75 V ® -0,95 V ® -1,05 V ® -1,2 V ® -0.95 V the coefficient of susceptibility of this steel to stress corrosion cracking KS increases correspondingly, 1,09 ® 1,11 ® 1,13 ® 1,26. The concentration of hydrogen which penetrating into steel at these potentials changes nonmonotonically: 0 ® 0 ® 0,057 ® 0,018 mol/dm3. The rate of residual corrosion with a potential shift in the series Еcor ® -0,75 V ® -0,95 V ® -1,05 V decreases first sharply, then slowly: 0.035 mm/year ® 0.005 mm/year ® 0.0009 mm/year ® 0.0004 mm/year, i.e. at high cathodic potentials, the applied polarization is spent on the decomposition of the aqueous electrolyte with the release of hydrogen, which penetrates into the steel and causes brittle cracking, which is confirmed by an increasing in the part of brittle fracture in the surface morphology of the specimens. Scientific originality. New results of fundamental research concerning the regularities of stress-corrosion cracking of ferrite-pearlite class steel of pipe assortment 10G2FB under conditions of cathodic protection in the range of potentials from the corrosion potential to -1.2 V have been obtained. It was revealed that a feature of the effect of cathodic polarization in the indicated range of potentials when assessing the tendency to stress corrosion cracking by the KS coefficient is an increasing in the relative narrowing and a decrease in the relative elongation, which generally indicates the embrittlement of the metal under the contact with corrosive medium and potential. Strength characteristics remain almost the same. The greatest tendency to stress-corrosion cracking is observed at a polarization potential of -1.0 V or more negative. Practical value. The developed methodology for a complex study of the regularities of stress- corrosion cracking was used for study of 10G2FB steel of the pipe assortment in a model soil environment NS4 under conditions simulating operating conditions. The new data obtained on the regularities of stress-corrosion cracking of steel will be useful for preventing the stress-corrosion cracking of main gas pipelines during operation.